2015
DOI: 10.4236/ojmetal.2015.53003
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sintering Temperature on the Densification of Mechanically Alloyed W-Brass Composites

Abstract: Prealloyed (PA) and premixed (PM) W-brass with the composition of 60 wt% W, 1 wt% Ni and 39 wt% brass was sintered at the temperature of 800˚C, 920˚C and 1000˚C each. As a result of difficulties in the densification of W-Cu and W-Cu alloys, mechanical alloying (MA) and activated sintering were combined. The powders were mechanically alloyed for 13 hours to produce nanosized W grains embedded in brass. The microstructure and properties of these composites with increase in sintering temperature has been studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Regardless of the good electrical and thermal properties of copper, it suffers from high coefficient of thermal expansion and low mechanical properties, which decreases the lifespan of its component. 15…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the good electrical and thermal properties of copper, it suffers from high coefficient of thermal expansion and low mechanical properties, which decreases the lifespan of its component. 15…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the sintering temperature on the density of the copper-tungsten composite in an argon and hydrogen atmosphere was studied, and the results showed that the sintered density was positively affected by increasing the sintering temperature. 3,4,14…”
Section: Introductionmentioning
confidence: 99%